Efektivitas Pemberian Minyak Zaitun Dan Lidah Buaya Terhadap Pemudaran Stretch Mark Pada Ibu Nifas Di Wilayah Kerja Puskesmas Krueng Barona Jaya Aceh Besar - Syarifah Masthura; Nurdia Wati; Nursa’adah Nursa’adah (The Journal General Health and Pharmaceutical Sciences Research, 2024)
Stretch marks experienced by most women on their post-pregnancy and childbirth. A stretch mark is a type of scar that appears physiologically on the skin. The scar is not harmful; however, if it is not taken care of properly, the stretch marks will become the problem. Thus, pharmacology and non-pharmacological treatments are needed to overcome this state. Olive oil and aloe vera use as non-pharmacological treatments. They are known as a safe and effective treatment to eliminate stretch marks on pregnant and postpartum women. This study aims to determine the effectiveness of olive oil and aloe vera for a treatment to get rid of stretch marks among postpartum women in Krueng Barona Jaya Public Health Centre, Aceh Besar. The method used was pre-experimental research with one group pre-test–post-test design. The population was 47 postpartum women chosen using a purposive sampling technique. The sample was 15 respondents with stretch marks. The research conducted from August 16 - 22, 2023. The result of univariate analysis shows that 10 out of 15 women had severe stretch marks (66,7%). Thus, after the treatment by applying olive oil and aloe vera as the healing treatment, the stretch marks seems to be gone from indicated by the result from 5 respondents (66,7 %) of pregnant and postpartum. Thus, the result of the Wilcoxon test shows a P-value 0,025. It means that olive oil and aloe vera are very effective to use as the alternative to eliminate the stretch marks on pregnant and postpartum women.